Biosynthesized silver and gold nanoparticles are potent antimycotics against opportunistic pathogenic yeasts and dermatophytes - Rónavári A (Dove Medical Press, 2018)
Andrea Rónavári,1,2 Nóra Igaz,2 Mohana Krishna Gopisetty,2 Bettina Szerencsés,3 Dávid Kovács,2 Csaba Papp,3 Csaba Vágvölgyi,3 Imre Miklós Boros,2,4 Zoltán Kónya,1,5 Mónika Kiricsi,2 Ilona Pfeiffer3 1Department of Applied and Environmental Chemistry, 2Department of Biochemistry and Molecular Biology, 3Department of Microbiology, Faculty of Science and Informatics, University of Szeged, Szeged, 4Institute of Biochemistry, Biological Research Centre of the Hungarian Academy of Sciences, 5MTA-SZTE Reaction Kinetics and Surface Chemistry Research Group, Szeged, Hungary Background: Epidemiologic observations indicate that the number of systemic fungal infections has increased significantly during the past decades, however in human mycosis, mainly cutaneous infections predominate, generating major public health concerns and providing much of the impetus for current attempts to develop novel and efficient agents against cutaneous mycosis causing species. Innovative, environmentally benign and economic nanotechnology-based approaches have recently emerged utilizing principally biological sources to produce nano-sized structures with unique antimicrobial properties. In line with this, our aim was to generate silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs) by biological synthesis and to study the effect of the obtained nanoparticles on cutaneous mycosis causing fungi and on human keratinocytes. Methods: Cell-free extract of the red yeast Phaffia rhodozyma proved to be suitable for nanoparticle preparation and the generated AgNPs and AuNPs were characterized by transmission electron microscopy, dynamic light scattering and X-ray powder diffraction. Results: Antifungal studies demonstrated that the biosynthesized silver particles were able to inhibit the growth of several opportunistic Candida or Cryptococcus species and were highly potent against filamentous Microsporum and Trichophyton dermatophytes. Among the tested species only Cryptococcus neoformans was susceptible to both AgNPs and AuNPs. Neither AgNPs nor AuNPs exerted toxicity on human keratinocytes. Conclusion: Our results emphasize the therapeutic potential of such biosynthesized nanoparticles, since their biocompatibility to skin cells and their outstanding antifungal performance can be exploited for topical treatment and prophylaxis of superficial cutaneous mycosis. Keywords: antifungal activity, biological synthesis, dermatophytes, opportunistic pathogenic yeasts, silver nanoparticles, toxicity